PEMBERDAYAAN MASYARAKAT DESA HUTAN MELALUI SISTEM TUMPANGSARI UNTUK MEWUJUDKAN KETAHANAN PANGAN TINGKAT MIKRO DI KABUPATEN PEMALANG - Fibriani Saraswati; Wiwik Widayati; Nunik Retno H (Journal of Politic and Government Studies, 2014)
Food crisis issues in Indonesia caused by the lack of diversification and reduced agricultural land can be overcome with the use of forest land through intercropping system in which at the same time there is empowering of the village community forest. Empowerment for the community forest village itself consists of the provision of access and capacity enhancement.This study used qualitative research methods with a phenomenological approach. Through this method will be investigated regarding the empowerment of forest villagers to achieve food security at their household level through the experiences, behaviors, and their perceptions.Empowerment conducted in forest village communities in all district has been running for the maximum in terms of providing access to the provision of access to working the land in the forest area in the form of establishment of the service implementation is given work area as well as licensing. While in terms of improvement through facilitation has not running optimally, especially market and capital access, as well as business development.Differences crop intercropping utilization results from the empowerment of forests village communities provide different contributions to food security at their household level, especially on the dimensions of accessibility and availability of food. Keywords: Empowerment, Forest Village Communities, and Food Security